Effectiveness of Meditation Techniques in Treating Post-Traumatic Stress Disorder: A Systematic Review and Meta-Analysis - David W. Orme-Johnson; Vernon A. Barnes; Brian Rees; Jean Tobin; Kenneth G. Walton (Medicina)
Background and Objectives: Post-traumatic stress disorder (PTSD) is a debilitating condition worldwide. The limited effectiveness of current psychological and pharmacological treatments has motivated studies on meditation techniques. This study is a comprehensive, multiple-treatments meta-analysis comparing the effectiveness of different categories of meditation in treating PTSD. Methods and Materials: We followed Prisma guidelines in our published protocol to search major databases and to conduct a meta-analysis of the studies. Results: We located 61 studies with 3440 subjects and divided them logically into four treatment groups: Mindfulness-Based Stress Reduction (MBSR, 13 studies); Mindfulness-Based Other techniques (MBO, 16 studies), Transcendental Meditation (TM, 18 studies), and Other Meditations that were neither mindfulness nor TM (OM, 14 studies). Trauma populations included war veterans, war refugees, earthquake and tsunami victims, female survivors of interpersonal violence, clinical nurses, male and female prison inmates, and traumatized students. Of those offered, 86% were willing to try meditation. The baseline characteristics of subjects were similar across meditation categories: mean age = 52.2 years, range 29–75; sample size = 55.4, range 5–249; % males = 65.1%, range 0–100; and maximum study duration = 13.2 weeks, range 1–48. There were no significant differences between treatment categories on strength of research design nor evidence of publication bias. The pooled mean effect sizes in Hedges’s g for the four categories were MBSR = −0.52, MBO = −0.66, OM = −0.63, and TM = −1.13. There were no appreciable differences in the study characteristics of research conducted on different meditations in terms of the types of study populations included, outcome measures, control conditions, gender, or length of time between the intervention and assessment of PTSD. TM’s effect was significantly larger than for each of the other categories, which did not differ from each other. No study reported serious side effects. Conclusions: All categories of meditation studied were helpful in mitigating symptoms of PTSD. TM produced clinically significant reductions in PTSD in all trauma groups. We recommend a multisite Phase 3 clinical trial to test TM’s efficacy compared with standard treatment.